2021
DOI: 10.3390/v13020161
|View full text |Cite
|
Sign up to set email alerts
|

Interactions of Influenza and SARS-CoV-2 with the Lung Endothelium: Similarities, Differences, and Implications for Therapy

Abstract: Respiratory viruses such as influenza and severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) are a constant threat to public health given their ability to cause global pandemics. Infection with either virus may lead to aberrant host responses, such as excessive immune cell recruitment and activation, dysregulated inflammation, and coagulopathy. These may contribute to the development of lung edema and respiratory failure. An increasing amount of evidence suggests that lung endothelial cells play a cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 198 publications
(229 reference statements)
0
16
0
1
Order By: Relevance
“…There are no practical clinical guidelines to manage the viral coinfection in COVID-19 patients, and their treatment takes place based on previous experience learned from other outbreaks including influenza and SARS [4].…”
Section: Introductionmentioning
confidence: 99%
“…There are no practical clinical guidelines to manage the viral coinfection in COVID-19 patients, and their treatment takes place based on previous experience learned from other outbreaks including influenza and SARS [4].…”
Section: Introductionmentioning
confidence: 99%
“…Vasculotides is an Ang-1 mimetic provided with an anti-inflammatory effect. In animal models, it has been found to be helpful in various conditions such as hemorrhagic shock, pneumonia [222,223], strokes [224,225], and in preventing pathologic vascular leakage [226,227].…”
Section: Angiopoietin1 Mimeticsmentioning
confidence: 99%
“…Some countries take COVID-19 as an influenza, but extensive disease characterization data and research have shown that COVID-19 is not comparable to pandemic influenza, either in terms of its health hazards or its potential harm to society (Latreille and Lee, 2021). Evidence indicated that synthetic biology techniques play an important role in developing sensitive and specific diagnostic kits, vaccines and therapeutic drugs during the fighting against COVID-19.…”
Section: Synthetic Biology Involved In Pathogen Identification and Vaccine Developmentmentioning
confidence: 99%